MALEIC HYDRAZIDE DAN RESPON PEMBUNGAAN KACANG TANAH (Arachis hypogaea L.) KULTIVAR TIGO AMPEK - Erda Muhartati (JURNAL BIOSENSE, 2026)
The limitations of manual emasculation techniques that are less effective in peanuts, especially the Tigo Ampek variety, encourage the application of Maleic Hydrazide as an alternative to increase flowering and production yields. This study aims to examine the effect of concentration, application time, and the interaction between the two on the growth and flower production of the Tigo Ampek variety of peanuts. The method used was a factorial Completely Randomized Design with 18 treatments and 3 replications. The results showed the highest decrease in the number of flowers (40.67) in the 350 ppm treatment with three applications.